Metabolism of drugs and other xenobiotics in giant liver fluke (Fascioloides magna) - Prchal, Lukáš; Vokřál, Ivan; Kašný, Martin; Rejšková, Lenka; Zajíčková, Markéta; Lamka, Jiří; Skálová, Lenka; Lecová, Lenka; Szotáková, Barbora (Xenobiotica; the fate of foreign compounds in biological systems, 2016)
1. Giant liver fluke Fascioloides magna is a dangerous parasite, which infects herbivores. It was imported to Europe from North America and started to spread. Benzimidazoles like albendazole, mebendazole, triclabendazole and salicylanilides closantel and rafoxanide are the most used anthelmintics to control fascioloidosis. However their effect might be altered via drug-metabolizing enzymes of this parasite. 2. The aim of our study was to determine the activities of drug-metabolizing enzymes in F. magna and the metabolism of above mentioned anthelmintics. 3. Activities of several oxidative, reductive and conjugative enzymes towards various model xenobiotic substrates were found in F. magna subcellular fractions. 4. Subcellular fractions from F. magna oxidized albendazole to its sulphoxide metabolite and reduced mebendazole to hydroxyl-mebendazole. Under ex vivo conditions, only very-low concentrations of these compounds were detected using high-performance liquid chromatography/mass spectrometry. 5. The results indicate that the giant liver fluke possesses the active xenobiotic-metabolizing system. The overexpression of this system may play an important role in parasite resistance against these anthelmintics.
Keywords: Chromatography, High Pressure Liquid; Triclabendazole; sulfoxidy; Benzimidazoles; Albendazole; Rafoxanide; triklabendazol; Xenobiotics; zvířata; biotransformation; mebendazole; Anthelmintics; benzimidazoly; rafoxanid; Sulfoxides; mebendazol; anthelmintika; albendazol; Mebendazole; xenobiotika; drug-metabolizing enzymes; salicylanilidy; Salicylanilides; Animals; anthelmintics; Fasciola hepatica; vysokoúčinná kapalinová chromatografie